Identifying the impact of external environment on business angel activity - Zinecker, Marek; Skalická, Martina; Balcerzak, Adam Przemyslaw; Pietrzak, Michał Bernard (Taylor & Francis, 2021)
We intend to contribute the empirical evidence in regard to identifying the impact of external environment on the activity of business angels in Czechia. Although prior academic studies have argued that e.g. overall economic growth, capital market, legal structures and the protection of property rights, corruption, innovativeness, the tax rate and labour market policy are the main determinants of the decision-making of business angels in the well-developed market, little is known about exogenous factors affecting behaviours of informal venture capitalists in Central and Eastern European countries. To our knowledge, we are the first who attempt to uncover the perception of changing economic conditions on business angel decision-making while using a qualitative survey research approach as primary data on business angels is currently not available. The results indicate that business angels pay little attention to the impact of the general macroeconomic conditions, as well as the role played by the capital market. They refer to ‘critical’ issues related to the difficult predictability of legislative changes. Dissatisfaction has also been expressed with the functioning of the public administration. Business angels also consider the current situation on the labour market and public education policy to be serious barriers to business development in the Czech Republic.

We intend to contribute the empirical evidence in regard to identifying the impact of external environment on the activity of business angels in Czechia. Although prior academic studies have argued that e.g. overall economic growth, capital market, legal structures and the protection of property rights, corruption, innovativeness, the tax rate and labour market policy are the main determinants of the decision-making of business angels in the well-developed market, little is known about exogenous factors affecting behaviours of informal venture capitalists in Central and Eastern European countries. To our knowledge, we are the first who attempt to uncover the perception of changing economic conditions on business angel decision-making while using a qualitative survey research approach as primary data on business angels is currently not available. The results indicate that business angels pay little attention to the impact of the general macroeconomic conditions, as well as the role played by the capital market. They refer to ‘critical’ issues related to the difficult predictability of legislative changes. Dissatisfaction has also been expressed with the functioning of the public administration. Business angels also consider the current situation on the labour market and public education policy to be serious barriers to business development in the Czech Republic.
Identifying the impact of external environment on business angel activity
Keywords: Business angels; investment; macroeconomics; institutions; law; survey; Central and Eastern Europe; Business angels; investment; macroeconomics; institutions; law; survey; Central and Eastern Europe